1974
DOI: 10.1203/00006450-197404000-00664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Narcotic Withdrawal on Neonatal Sleep Patterns

Abstract: It i s known t h a t morphine and related compounds suppress REM sleep i n the adult. This study was undertaken t o determine if infants of heroin and methadone-addicted mothers would exhib i t a l t e r e d sleep patterns i n withdrawal. EOG, EMG, and r e s p i ra t i o n were recorded by multichannel polygraph on 10 i n f a n t s (4 methadone, 6 heroin) f o r 2%-4 hr. periods p r i o r to, during, and a f t e r chlorpromazine therapy (2.0 mg/kg/d). It was found t h a t heroin and methadone o b l i t e r a t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The examination of sleep in opiate‐exposed infants described in the present study is the most recent (no other studies have been carried out over the last 11 years) and has overcome the limitations of the previous four studies in this area 7–10 11 The present study is the first to measure the amount of wakefulness and number of arousals in newborns during acute opiate withdrawal.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The examination of sleep in opiate‐exposed infants described in the present study is the most recent (no other studies have been carried out over the last 11 years) and has overcome the limitations of the previous four studies in this area 7–10 11 The present study is the first to measure the amount of wakefulness and number of arousals in newborns during acute opiate withdrawal.…”
Section: Discussionmentioning
confidence: 93%
“…There have been four studies that have examined sleep in newborn infants withdrawing from opiates 7–10 . Only two of the four studies used current and reliable techniques for measuring and scoring newborn sleep as outlined by Anders and associates 7,9,11 …”
Section: Introductionmentioning
confidence: 99%
“…14, 227 (1960); we used a modification of this technique involving small inconspicuous spots at the wing bases. 6. Age is determined by subtracting the date on which a butterfly was first captured from the date in question.…”
mentioning
confidence: 99%
“…Five (5.2 percent) experimental and five control individuals were captured by a nonvisual predator, a strategically located female orb-weaving spider (Argiope argentata, Araneae), during the course of the study. 16 (5), a recent study reported a decrease in REM in newborns exposed to heroin and methadone in utero (6). Consequently, the precise nature of sleep disturbance during narcotic withdrawal in neonates remains unclear;…”
mentioning
confidence: 99%
“…A significant decrease in QS and increased REM was found in neonates prenatally exposed to opiates, a profile shared by many newborn at high risk for central nervous system impairment [Schulman, 1969;Dinges et al, 1980]. A decrease in both QS and REM was found in new born babies born to addicted mothers [Sisson et al, 1974], Sisson con cluded that since protein synthesis is stimulated during REM, treatment of withdrawal may be essential not only to relieve symptoms but also to pro mote normal and necessary sleep patterns required for brain development [Mirmiran et al, 1983]. Disturbances of the sleep-wake pattern with increased motor activity during sleep and increased sleep complaints have also been found in children born to hypertensive mothers treated with clonidine or a-methyldopa [Huisjes et al, 1984;Shimohira, 1984], Despite growing literature in the field of human behavioral teratoge nicity it is very difficult to be certain about a causal relationship between pre-and perinatal drug exposure and behavioral outcomes.…”
Section: Development Of Behavioral States: Influence Of Drugsmentioning
confidence: 84%